Peran Strategis Sekretariat Dewan Perwakilan Rakyat Daerah Dalam Legal Drafting Peraturan Daerah: Studi Kasus Di Kabupaten Hulu Sungai Selatan - Zaki Yamani, Akhmad; Azis Kurniawan, Muhammad (Zona Law And Public Administration Indonesia, 2024)
This study examines the strategic role of Provincial Legislatives Council Secretariat in the legal drafting of regional regulations in Hulu Sungai Selatan Regency. Employing a qualitative approach with a case study design, this research analyzes the effectiveness of the DPRD Secretariat's role, the influencing factors, and the challenges. The findings revealed the DPRD Secretariat plays a crucial role in providing administrative, technical, and coordinative support in the process of drafting regional regulations. However, the effectiveness of this role is still constrained by the limittation of human resources, the complexity of regulatory harmonization, and the limitation of resources. This study proposes strategies to optimize the DPRD Secretariat's role through enhancing human resource capacity, strengthening inter-institutional coordination, and utilizing the information technology. The implications of optimizing this role are improving quality of regional legislation, the efficiency of legislative process, and enhancing responsiveness to community needs. This research contributes to a more comprehensive understanding of the role of supporting institutions in the regional legislative process and highlights the importance of strengthening institutional capacity in the context of regional autonomy